The Role Of Influencer Marketing, Electronic Word Of Mouth (E-WOM), And Fear Of Missing Out (FOMO) As Influencers Of Generation Z's Purchasing Decisions On SKIN1004 In Shopee E-Commerce - Dina Septia Wati; Mulyo Budi Setiawan (UNIVED Press, 2026)
This study aims to analyze the influence of influencer marketing, electronic word of mouth (E-WOM), and fear of missing out (FOMO) on Generation Z purchase decisions for SKIN1004 products on Shopee. This research used a quantitative approach with primary data collected through an online questionnaire. The sample consisted of 150 Generation Z respondents who had purchased SKIN1004 products through Shopee. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that influencer marketing has a positive and significant effect on purchase decisions with a coefficient of 0.272 and p-value of 0.000. E-WOM has a positive and significant effect with a coefficient of 0.209 and p-value of 0.001. FOMO also has a positive and significant effect with a coefficient of 0.216 and p-value of 0.006. These findings indicate that social influence, online consumer reviews, and trend-related psychological pressure shape Generation Z purchase decisions in e-commerce.